Combination of Immobilization Techniques of Xylanase by Entrapment and Covalent Binding on Alginate Hydrogel Beads - Mimi Sakinah, A. M.; Siti Sabrina, M. S. (2016)
Enzymes serving as biocatalysts and play an important roles in many industrial field. However, the limitation of enzyme usage due to its high cost and unstable conditions of soluble enzyme to harsh conditions lead to findings an alternative to enhance the enzyme efficiency by immobilization (insoluble enzyme). The present work reported a combination of immobilization technique of xylanase by entrapment and covalent binding on alginate hydrogel beads. Xylanase enzyme was effectively immobilized within the alginate hydrogel beads by entrapment and covalent binding on the surface of alginate beads using glutaraldehyde as a cross-linked agent. The effects of immobilization parameters include of sodium alginate concentration (% w/v), calcium chloride (M), and glutaraldehyde concentration (% w/v) were studied in order to obtain a better immobilization yield. These effects were studied using one-factor-at-one-time (OFAT) to obtain the best conditions for xylanase immobilization. The analysis of xylanase activity was determined using dinitrosalicyclic (DNS) acid reagent method. Maximal enzyme immobilization yield (>80 %) was achieved at 3.0 % w/v sodium alginate concentration, 0.3 M calcium alginate, and 9 % w/v of glutaraldehyde concentration. The study shows the xylanase can be immobilized efficiently by a combination of immobilization techniques by entrapment and covalent binding on alginate hydrogel beads